The Upper Atmospheric Fountain Effect in the Polar Cusp Region - Rentz, Stefanie (2009)
This thesis examines how the cusp as a feature of the Earth Magnetic Field influences the (neutral) upper atmospheric dynamics. The thermospheric total mass density, as derived from CHAMP satellite data, shows a distinct enhancement in the vicinity of the cusp, the so-called density anomaly. In a climatological analysis this anomaly is identified as a continuous phenomenon of both hemispheres which depends mainly on background density, coupling efficiency between Earth Magnetic Field and Interplanetary Magnetic Field, and solar activity. Air-upwelling from deeper atmospheric layers (neutral fountain effect), as excited by Joule heating, is considered to be the cause of the density anomaly. Its activating mechanisms have been investigated by considering a combined CHAMP-EISCAT campaign, a model study on soft particle precipitation, and an analysis of periodic density anomaly variations and their controlling parameters. According to the results of this study the following mechanism is suggested to cause a cusp-related density anomaly: The energy input by the solar wind provides the power for Joule heating of preferably neutral molecules. Soft particle precipitation in the cusp simultaneously enhances the altitude of maximal Pedersen conductivity, thus lifting up the heated layer in the cusp. Differential expansion of heavier particles changes the local air composition, thus contributing to the density anomaly. The mechanism is more pronounced during high solar activity phases, since a larger background density causes larger density anomaly amplitudes. The phenomenon can affect the global thermospheric density distribution. Diese Arbeit untersucht, inwiefern die Cusp als Merkmal des Erdmagnetfeldes die Dynamik der (neutralen) Hochatmosphäre beeinflusst. Die aus CHAMP-Satellitendaten abgeleitete thermosphärische Gesamtmassendichte zeigt eine markante Erhöhung im Bereich der Cusp, die sogenannte Dichteanomalie. In einer klimatologischen Analyse wird diese Anomalie als kontinuierliches Phänomen beider Hemisphären ...